2008
DOI: 10.1007/s12033-007-9024-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Sequence and Functional Analysis of Goat ATP-binding Cassette Transporter G2 (ABCG2)

Abstract: ATP-binding cassette transporter G2 (ABCG2) gene encodes a protein that has a wide variety of substrates and is responsible for the active secretion of clinically and toxicologically important molecules into milk. Although known in many species, this marks the first time this gene product has been reported in goats. In this study, we cloned and sequenced goat ABCG2 gene complete coding sequence and predicted its putative translated protein structure with implicative functional domains. One six-transmembrane sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Motif Scan was also used to detect functional domains. Several phosphorylation sites and glycosylation sites were present, which may be important for targeting of the protein to the membrane [19]. In the full transporter, 14 N-glycosylation sites were found, out of which 2 sites (aa 85–88, 91–94) may be important for targeting of the transporter to the membrane (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motif Scan was also used to detect functional domains. Several phosphorylation sites and glycosylation sites were present, which may be important for targeting of the protein to the membrane [19]. In the full transporter, 14 N-glycosylation sites were found, out of which 2 sites (aa 85–88, 91–94) may be important for targeting of the transporter to the membrane (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two or more alpha-helices wound around each other in a symmetrical manner make up the basic “coiled–coil” structure [22]. Coiled-coils have been predicted to exist at the N-terminus of the goat half-transporter ABCG2 and the investigators have discussed the possibility that these domains may be involved in oligomerization functions [23]. A unique feature of the ABCB5 beta form is that it has 2 NBDs (first NBD lacking the Walker A) rather than the conventional 1 NBD, which is usually present in half-transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being a highly conserved transporter (Wu et al 2008), there is an increasing number of studies that describe differences in function and specificity of ABCG2 in different species (Schnepf & Zolk 2013;Wassermann, Halwachs, Baumann, et al 2013). In vitro cell models have been generated for the identification of ABCG2 substrates using transcellular transport mediated by the caprine and bovine ABCG2 and its Y581S variant Wassermann, Halwachs, Baumann, et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…ABCG2 is expressed several tissue including mammary gland and it is reported that the level of expression is elevated in lactation period in some monogastrics, goats and dairy cows [9][10][11] . Due to its function and near chromosomal location to an important QTL region effects on milk production traits in cattle [12,13] , researches have been focused on associations between mutations occur in the ABCG2 gene and milk production traits.…”
Section: Makale Kodu (Article Code): Kvfd-2014-8898mentioning
confidence: 99%